The influence of ocean anoxia on conditions for the Domanik deposits formation - Irina N. Plotnikova; Sergei B. Ostroukhov; Nikita V. Pronin (Записки Горного института)
The article considers one of conditions for the Domanik facies formation on the example of Tatarstan and Bashkortostan. The main emphasis is on the influence of anoxic paleobasin conditions on the high-carbon strata formation. A detailed study of the hydrocarbon composition of Domanik deposits made it possible to find characteristic biomarkers in their composition. They are based on the composition and structure of diagenetic products of biological compounds composing the sulphur bacteria living in anoxic/euxinic paleobasin conditions. Such compounds include C40 diaryl isoprenoids – isorenieratane and paleorenieratane. C10 tetramethylbenzenes also occupy a special place in the Domanik deposits study. Their appearance in the composition of organic matter of these deposits results from the transformation of sulphur bacteria compounds. Diaryl isoprenoids and tetramethylbenzenes are a reliable indicator of anoxic conditions of the Domanik deposits formation. The thermodynamic state of the hydrocarbon environment can be determined from the ratio of tetramethylbenzene isomers.